Improving The Achievement of Natural Science Learning on Plant Reproduction using Demonstration Method on Grade VI Students at Public Elementary school 7 of Patokan in The First Semester of 2015/2016 Academic Year - Slamet Slamet (Pancaran Pendidikan, 2018)
Natural science was concerned with finding out the nature sistematically, so natural science was not only the mastery of a knowledge collection of facts, concepts or principles but also a process of discovery. Natural science learning might be conducted in scientific inquiry to cultivate the ability to think, work and be scientific and communicate it as an important aspect of life skills.The demonstration method was a way of presenting the lesson by demonstrating and showing the students of a particular process, situation or object learned in the actual form or in the form of an imitation shown by the teacher or other learning resources who was expert in the topic of discussion to be demonstrated.Meanwhile the objective of this research was: to know the improving of natural science learning result of plant reproductionusing demonstration learning method on grade VI students of SDN 7 Patokan Situbondo subdistrict Situbondo regency in first semester of2015/2016 academic year.This research used action research as much as two circles. This research target was  the grade VI students of SDN 7 Patokan Situbondo subdistrict Situbondo regency in first semester of 2015/2016 academic year. Data were obtained in the form of formative test results, observation sheet of teaching and learning activities.From the analysis results were obtained that the students learning result improved from cycle I to cycle II. It was marked by the improving of students’ achievement in cycle I obtained an average score of 71.81 with 62.5% complete learning and on the second cycle improved with an average score of 74.93 with 87.5% mastery.